Ultraviolet light and ocular diseases - Yam, Jason C. S.; Kwok, Alvin K. H. (International ophthalmology, 2014)
The objective of this study is to review the association between ultraviolet (UV) light and ocular diseases. The data are sourced from the literature search of Medline up to Nov 2012, and the extracted data from original articles, review papers, and book chapters were reviewed. There is a strong evidence that ultraviolet radiation (UVR) exposure is associated with the formation of eyelid malignancies [basal cell carcinoma (BCC) and squamous cell carcinoma (SCC)], photokeratitis, climatic droplet keratopathy (CDK), pterygium, and cortical cataract. However, the evidence of the association between UV exposure and development of pinguecula, nuclear and posterior subcapsular cataract, ocular surface squamous neoplasia (OSSN), and ocular melanoma remained limited. There is insufficient evidence to determine whether age-related macular degeneration (AMD) is related to UV exposure. It is now suggested that AMD is probably related to visible radiation especially blue light, rather than UV exposure. From the results, it was concluded that eyelid malignancies (BCC and SCC), photokeratitis, CDK, pterygium, and cortical cataract are strongly associated with UVR exposure. Evidence of the association between UV exposure and development of pinguecula, nuclear and posterior subcapsular cataract, OSSN, and ocular melanoma remained limited. There is insufficient evidence to determine whether AMD is related to UV exposure. Simple behaviural changes, appropriate clothing, wearing hats, and UV blocking spectacles, sunglasses or contact lens are effective measures for UV protection.